Misdiagnosis of Psychosis and Obsessive-Compulsive Disorder in a Young Patient with Autism Spectrum Disorder - Jiangbo Ying; Melvyn Weibin Zhang; Sreedharan Geetha Sajith; Giles Ming-Yee Tan; Ker-Chiah Wei (Case Reports in Psychiatry)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by deficits in social interaction and the presence of restricted and repetitive patterns of behavior. Making a first diagnosis of ASD in adults has certain difficulties, including inaccurate recall of developmental history and overlapping behaviors with other psychiatric conditions. This case study presents a young man who was assessed to have no major mental illness during his first visit to emergency services in a psychiatric hospital. During his second visit, he was initially assessed to have first episode psychosis, due to his possible delusional beliefs related to the insurance payout, social withdrawal, and strange behaviors, and then later he was assessed to have obsessive-compulsive disorder (OCD) instead of psychosis, because of his recurrent and intrusive thoughts. Eventually, his diagnosis was revised to ASD during outpatient follow-up after more comprehensive assessment. It is not easy to differentiate ASD from psychosis among some adult patients, even for expert psychiatrists. Cognitive rigidity in ASD may be similar to delusions in psychosis. Unusual behaviors in ASD can be confused with disorganized behaviors in psychosis. Differentiating ASD from OCD can be a complicated task as well, due to similarities between ASD and OCD. Restricted interests and repetitive behaviors in ASD may be perceived as obsessions and compulsions in OCD. Overall, diagnosis of ASD in adults requires comprehensive evaluation. Distinguishing symptoms of OCD and psychosis from autistic traits is critical for accurate diagnosis and optimal treatment. Although research in adult ASD has expanded alongside increased prevalence statistics over the past few years, more efforts to enhance the diagnostic processes in adult ASD are needed to reduce the challenges in this field.